Attitude of Agriculture Collegian towards Opting Farming as a Profession - S. K , Deena Dayalan.; Devarani , L.; Singh, R.J.; Feroze, S.M. (Indian Journal of Extension Education, 2018)
Most agriculture graduates are absorbed in public and private sector jobs and only few are observed to have actually taken  up farming as a life work which is in agreement to the general belief that farming is a non-professional, less prestigious and  less profitable career to be taken up by the students after their graduation. Thus this exploratory study was carried out  purposively on the B.Sc. (Agriculture) fourth year students in College of Agriculture, Imphal which is one of the allied  colleges of Central Agricultural University, Imphal to study the attitude of agriculture collegian towards opting farming as  a profession through personal interview of the respondents. From the study it is found that 90.62 per cent of the  respondents had favourable attitude towards opting farming as a profession. From the study it is concluded that efforts are  required to convert the covert attitude into overt behaviour such that graduates adopt farming as their profession so as to  harness the potential of graduates and agriculture at the same time.
Keywords: Agriculture; attitude; collegian; farming; profession